PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN: THE EFFECT OF LIQUIDITY, COMPANY SIZE AND PROFITABILITY ON FIRM VALUE - Siti Nurjanah; Ceacilia Srimindarti (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study aims to determine the relationship between liquidity, firm size, and profitability to firm value. The population used in this study is a state-owned company listed on the Indonesia Stock Exchange during 2017 – 2021. There are 20 state-owned companies listed on the Indonesia Stock Exchange, but there are 3 companies that do not meet the predetermined criteria so that 85 is obtained sample. The sampling technique used was purposive sampling and analyzed using SPSS version 21. The results of this study states that liquidity has a positive effect on firm value, meanwhile company size and profitability have no effect on value state-owned companies listed on the Indonesia Stock Exchange (IDX) in 2017 - 2021.